2020
DOI: 10.1186/s13014-020-01563-x
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for nonagenarians: the value of biological versus chronological age

Abstract: Background: The number of nonagenarian cancer patients (≥ 90 years) is continuously increasing, and radiotherapy is performed in a relevant proportion of patients, as surgery and chemotherapy are often not feasible for these patients. However, the evidence regarding the feasibility and treatment outcomes after radiotherapy for this patient group is very limited. Methods: All nonagenarian patients receiving (chemo) radiotherapy between 2009 and 2019 at the University of Freiburg-Medical Center were analyzed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Of these 27 patients, 16 received adjuvant radiotherapy, while 11 underwent adjuvant/additive chemoradiotherapy either due to R1 resection ( n = 1) or due to extranodal extension ( n = 11; one patient exhibited both R1 resection and extranodal extension). As described previously, completion rates for both radiotherapy and chemotherapy were very high with 96% and 97%, respectively [ 49 , 50 ]. Detailed patient and treatment characteristics can be found in Table 3 .…”
Section: Methodsmentioning
confidence: 79%
“…Of these 27 patients, 16 received adjuvant radiotherapy, while 11 underwent adjuvant/additive chemoradiotherapy either due to R1 resection ( n = 1) or due to extranodal extension ( n = 11; one patient exhibited both R1 resection and extranodal extension). As described previously, completion rates for both radiotherapy and chemotherapy were very high with 96% and 97%, respectively [ 49 , 50 ]. Detailed patient and treatment characteristics can be found in Table 3 .…”
Section: Methodsmentioning
confidence: 79%
“…The United States National Institute of Aging consensus definition subdivides between "young old" (65-74 years), "older old" (75-84 years) and "oldest old" (≥ 85 years) (23). Recent literature often extends this by the socalled nonagenarian patient older than 90 years (24,25). The clinical implication of this arbitrary classification is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Besides lymph node involvement, age was the second strong prognostic parameter for OS in our analysis. Given the very advanced age of our patient cohort, OS values are likely due to the non-cancer mortality of our elderly patients [ 30 , 31 ]. Similarly, Harris et al reported reduced OS and a trend towards reduced LRC in patients older than 70 years treated with adjuvant radiotherapy for cSCC, thus supporting our data [ 18 ].…”
Section: Discussionmentioning
confidence: 99%